Pterostilbene Attenuates Astrocytic Inflammation and Neuronal Oxidative Injury After Ischemia-Reperfusion by Inhibiting NF-κB Phosphorylation - Liu, Haixiao; Wu, Xun; Luo, Jianing; Wang, Xiaogang; Guo, Hao; Feng, Dayun; Zhao, Lei; Bai, Hao; Song, Mingyang; Liu, Xunyuan; Guo, Wei; Li, Xia; et al. (Frontiers in Immunology, 2019)
Astrocyte-mediated inflammation and oxidative stress elicit cerebral ischemia-reperfusion (IR) injury after stroke. Nuclear factor (NF)-κB activates astrocytes and generates pro-inflammatory factors. The purpose of the present study is to elucidate the effect of pterostilbene (PTE, a natural stilbene) on astrocytic inflammation and neuronal oxidative injury following cerebral ischemia-reperfusion injury. A middle cerebral artery occlusion-reperfusion (MCAO/R) mouse model and HT22/U251 co-culture model subjected to oxygen-glucose deprivation and re-introduction (OGD/R) were employed, with or without PTE treatment. The data showed that PTE delivery immediately after reperfusion, at one hour after occlusion, decreased infarct volume, brain edema, and neuronal apoptosis, and improved long-term neurological function. PTE decreased oxidation (i.e., production of reactive oxygen species, malondialdehyde) and inflammatory mediators (tumor necrosis factor-α, interleukin-1β, and interleukin-6), and increased anti-oxidative enzyme activities (i.e., of superoxide dismutase, glutathione peroxidase), by inhibiting phosphorylation and nuclear translocation of NF-κB. In conclusion, PTE attenuated astrocyte-mediated inflammation and oxidative injury following IR, via NF-κB inhibition. Overall, PTE is a promising neuroprotective agent.